Illness perceptions associated with patient burden with musculoskeletal pain in outpatient physical therapy practice, a cross-sectional study. (February 2020) - de Raaij, E.J.; Ostelo, R.W.J.G.; Maissan, J.F.; Pool, J.; Westers, P.; Wittink, H.
Abstract: Introduction: Musculoskeletal pain (MSP) is a burden to patients and to society. In addition to well-known prognostic factors, illness perceptions (IPs) may be associated with pain intensity and physical functioning in MSP but their role is not fully understood. Our research focused on these questions: 1) Do IPs differ between patients with acute, sub-acute and persistent MSP 2) Are IPs, in addition to well-known prognostic factors, associated with pain intensity and with limitations in physical functioning? Methods: Eligible MSP patients from 29 physical therapy practices were invited to participate in a cross-sectional study. IPs were measured with the Brief IPQ-DLV. We compared IPs between patients with acute, sub-acute and persistent MSP (1-way ANOVA with Tukey post-hoc tests). Secondly, associations between IPs with pain intensity and physical functioning were assessed (multiple linear regression). Results: With 658 participants, most IP dimensions showed small differences between acute, sub-acute or persistent pain. For pain intensity, the IP dimensions Consequences, Identity and Comprehensibility explained an additional 13.3% of the variance. For physical functioning, the dimensions Consequences, Treatment Control, Identity and Concern explained an additional 26.5% of the variance. Discussion/conclusion: Most IP dimensions showed small differences between acute, sub-acute or persistent pain. In addition to some well-known prognostic variables, higher scores on some IP dimensions are associated with higher pain intensity and more limitations in physical functioning in patients with MSP. Longitudinal studies are needed to explore the longitudinal associations. Highlights: Illness perceptions are clinically not relevant different according to pain duration. Consequences, Identity and Comprehensibility contribute to pain intensity. Consequences, Identity, Treatment Control and Concern contribute to physical functioning.